A global chromoblastomycosis strategy and development of the global chromoblastomycosis working group. - Dallas J Smith; Flávio Queiroz-Telles; Fahafahantsoa Rapelanoro Rabenja; Roderick Hay; Alexandro Bonifaz; Marlous L Grijsen; Romain Blaizot; Fernando Messina; Yinggai Song; Shawn R Lockhart; Alexander Jordan; Alyson M Cavanaugh; et al. (Public Library of Science (PLoS), 2024)
Chromoblastomycosis, an implantation mycosis, is a neglected tropical disease that causes decreased quality of life, stigma, and disability. The global burden of disease is unknown and data on disease epidemiology and outcomes are severely limited by a lack of access to needed diagnostic tools and therapeutics. The World Health Organization outlined targets for chromoblastomycosis in the Road Map for Neglected Tropical Diseases 2021-2030, but little progress has been made in initiating and implementing an effective control program globally. This lack of guiding policy and progress led to the recent formation of a Global Chromoblastomycosis Working Group which has developed a global chromoblastomycosis strategy. We describe this strategy, which outlines specific steps needed to improve technical progress, strategy and service delivery, and enablers. Clinicians, researchers, public and government officials, patients, and policy makers can align their time, expertise, and resources to improve the lives of communities affected by chromoblastomycosis through this strategy.